Capturing physiology of emotion along facial muscles: a method of distinguishing feigned from involuntary expressions - Khan, Masood Mehmood; Ward, R.; Ingleby, M. (Springer Berlin, Heidelberg, 2009)
The ability to distinguish feigned from involuntary expressions of emotions could help in the investigation and treatment of neuropsychiatric and affective disorders and in the detection of malingering. This work investigates differences in emotion-specific patterns of thermal variations along the major facial muscles. Using experimental data extracted from 156 images, we attempted to classify patterns of emotion-specific thermal variations into neutral, and voluntary and involuntary expressions of positive and negative emotive states. Initial results suggest (i) each facial muscle exhibits a unique thermal response to various emotive states; (ii) the pattern of thermal variances along the facial muscles may assist in classifying voluntary and involuntary facial expressions; and (iii) facial skin temperature measurements along the major facial muscles may be used in automated emotion assessment.